1998
DOI: 10.3758/bf03206054
|View full text |Cite
|
Sign up to set email alerts
|

Relative size perception at a distance is best at eye level

Abstract: Relative size judgments were collected for two objects at 30.5 m and 23.8 m from the observer in order to assess how performance depends on the relationship between the size of the objects and the eye level of the observer. In three experiments in an indoor hallway and in one experiment outdoors, accuracy was higher for objects in the neighborhood of eye level. Weconsider these results in the light of two hypotheses. One proposes that observers localize the horizon as a reference for judging relative size, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 10 publications
2
39
0
3
Order By: Relevance
“…That is, EH may be the default scalar for objects within EH range. This notion is consistent with studies in visual perception, in which participants scaled target heights to EH even in the absence of an explicit intended action (Bertamini et al, 1998;.…”
Section: Implications Of Findingssupporting
confidence: 78%
See 2 more Smart Citations
“…That is, EH may be the default scalar for objects within EH range. This notion is consistent with studies in visual perception, in which participants scaled target heights to EH even in the absence of an explicit intended action (Bertamini et al, 1998;.…”
Section: Implications Of Findingssupporting
confidence: 78%
“…All parallel contours in a scene (except those normal to the line of sight) converge at the horizon, and for a forward-moving observer, all optically specified texture elements above EH move up, whereas those below EH move down. Bertamini, Yang, and Proffitt (1998) showed that observers are sensitive to EH when making relative height judgments. Their participants viewed two targets simultaneously and judged which target was taller.…”
Section: Eye-height Scaling In Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, eye height can provide a body-scaled metric for perceiving size. Bertamini, Yang, and Proffitt (1998) demonstrated that eye height provides a metric for relative size perception of objects viewed at a distance. They varied object height and egocentric distance, and perceivers judged which of two objects was taller.…”
Section: Body Scaling In Perceptionmentioning
confidence: 99%
“…Perrone (1982) has proposed a general model that explains the overestimation of visual slant as due to the misperception of eye level relative to the hill. Other research has provided related computational models that demonstrate that the perception of relative size is influenced by angular declination and eye level (Bertamini, Yang, & Proffitt, 1998;Ooi, Wu, & He, 2001). Proffitt et al (1995) and Bertamini et al also confirmed that hills are generally experienced as being steeper than they actually are, although hills are not judged to be so when haptic or motoric assessments are used.…”
Section: Slant Overestimationmentioning
confidence: 67%